STIGMA MASYARAKAT TERHADAP ANAK PENYANDANG DISABILITAS - Kurnia Utami Nursholichah; Amilia Febrian Mufarrohah; Bono Setyo (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
The purpose of this study was to determine the stigma of society towards children with disabilities in Bengkulu province. This study used a qualitative method with a case study approach. Data were collected through observation analysis, interviews, and documentation. Respondents in this study were the village head and three parents of children with disabilities. The results of the study indicate that the stigma towards children with disabilities in the Village is still very strong and includes various negative views, both towards children and their families. This stigma appears in the form of negative labels such as "stupid children," "naughty children," "cursed children," or "family burdens." These negative views are mainly influenced by factors such as public ignorance, lack of education about disabilities, and minimal empathy and sympathy in social interactions Keywords: Stigma; Children; Disability